Reform of Islamic Inheritance Law: The Influence of Customary Law on the Institution of Wasiat Wajibah in Islamic Law - Fatahullah; Adi Sulistiyono; Burhanudin Harahap (Magister of Law, Faculty of Law, University of Mataram, 2025)
This research aims to investigate the status of the deceased's close relatives, including adopted children, illegitimate children, and children of diverse religions, within the family structure and their legitimate legal standing, thereby establishing their entitlement to inherit the decedent's property. Nonetheless, the viewpoint of the inheritance legal framework in Indonesia about the status of these immediate relatives is markedly distinct. The employed methodology is a normative or doctrinal legal study utilizing a legislative approach and analysis. Wasiat wajibah is an institution in Islamic law in Indonesia to address the problem of differing paradigms between customary law, which recognises all positions and rights of adopted children, and Islamic law, which